Analisis Penerapan Akuntansi Keuangan Berdasarkan Standar Yang Berlaku Dalam Penyajian Laporan Keuangan (Studi Kasus Pada KSP Kopdit Suru Pudi Koting) - Maksima Toyo; Wilhelmina Mitan; Emilianus Eo Kutu Goo (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the application of financial accounting based on applicable standards in the presentation of financial statements at the Suru Pudi Koting Cooperative. This study used descriptive qualitative method. Data collection techniques used are interviews and documentation. The data analysis technique, namely qualitative data analysis, begins with the data reduction stage, data presentation and conclusion drawing and verification. The results of the study show that the Suru Pudi Koting cooperative has implemented SAK ETAP, but there are still some errors in the presentation of the balance sheet and calculation of operating results. The financial reports presented by the cooperative are not complete because they only apply 2 main reports, namely balance sheets and reports on calculation of operating results, while cash flow reports, changes in equity and notes on financial statements have not been implemented.